Islamic transformation centre: enhancing the knowledge and skills of rural school students by leveraging Quadruple Helix Model (QHM) collaboration - Asadullah, Mohamed; Norris, William; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2015)
The purpose of this paper is to enhancing the knowledge and the skills of rural school students by harnessing on capabilities of information and communication technology (ICT) via Islamic Transformation Centre (ITC). The important area focuses are mainly on the availability of information and communication technology tools to the rural schools in Malaysia. This will be in collaboration with the “whole-of-government” concept of information and communication technology (ICT) implementation across the schools in Malaysia mooted by Ministry of Education (MOE) and Ministry of Rural and Regional Development (MORARD) in understanding the plans and executions method to benefit the development of the rural schools in Malaysia. The paper is based on literature review, adopting the business model canvas (BMC) framework in building a conceptual solution for knowledge and skill development of the rural schools children. This paper explores the important collaboration of Quadruple Helix Model (QHM) in integration of Government, University, Industry and Citizen ICT infrastructure for education in rural schools, and the success rate of it.